OPTIMIZATION OF TEACHER'S ACTIVITIES IN EDUCATION EMOTIONALLY POSITIVE ATTITUDE OF STUDENTS TO TEACHING BY MEANS OF METHODICAL WORK OF SCHOOL (Pedagogy of Higher and Secondary Education, 2007)
The article theoretically bases the role of school's methodical work in up-growing of results of teacher's activity in up-bringing of schoolchildren of emotional and positive attitude to study; it bases the necessity of harmonization of intellectual and emotional factors in the process of study as an important mean of an effective up rising of a methodical work in security of a qualitative education.